SANTET DALAM KUHP BARU: ANALISIS KRIMINALISASI TERHADAP PELAKU YANG MENYATAKAN DIRINYA MEMPUNYAI KEKUATAN GAIB PADA PASAL 252 UNDANG-UNDANG NOMOR 1 TAHUN 2023 - Navadz Syaikhul Radzakani; Maria Novita Apriyani (Universitas Labuhanbatu, 2026)
The phenomenon of witchcraft or claims of having supernatural powers is a social reality that often causes unrest and deception in society. Article 252 of Law No. 1 of 2023 stipulates that anyone who claims to possess supernatural powers and offers services that could cause harm to others can be punished. Such actions are not judged based on the truth or falsehood of supernatural abilities, but rather on the act of claiming or offering services that could have legal consequences. This research aims to determine the elements of criminal acts that can be imposed on individuals who claim to possess supernatural powers (black magic), and the second research question is whether perpetrators who claim to have supernatural powers can be given criminal sanctions. This research uses a normative legal method with a statutory approach and a conceptual approach. Where the author uses primary legal materials such as Law No. 1 of 2023, secondary legal materials such as legal journals, and non-legal materials such as news related to the issue. The research results indicate that the existence of Article 252 of Law No. 1 of 2023 is a progressive step in addressing the social problems that have long been developing in Indonesian society. This regulation provides legal certainty and protects the public from disturbing and potentially criminal practices of witchcraft.Keywords: Criminalization, Perpetrator, Supernatural Power, Black Magic